Implications of LDH in patients with coronavirus disease 2019 pneumonia - Mu, Tong; Wang, Xingguang; Lu, Zhiming; Tong, Jia (Frontiers in Cellular and Infection Microbiology, 2023)
Objective The objective of this study was to explore the value of serum lactic dehydrogenase (LDH) in the early diagnosis and prognostic evaluation of pneumonia associated with the novel coronavirus infection. Methods A total of 101 patients with coronavirus disease 2019 (COVID-19) pneumonia were included in the study. According to the severity of the initial chest computed tomography (CT), the patients were divided into the ordinary pneumonia group and the severe pneumonia group and then divided into the remission group and the nonremission group according to the changes of the chest CT after medication treatment. The differences in general characteristics, underlying diseases, clinical symptoms, laboratory findings, and imaging examination outcomes between groups were observed retrospectively. To analyze the diagnostic performance of LDH, receiver operating characteristic (ROC) curves were constructed and the area under the curve (AUC) was calculated. Results Compared with ordinary pneumonia patients, patients in the severe group presented with significantly higher LDH, neutrophil count, high-sensitivity troponin T (HS-TnT), C-reactive protein (CRP), human serum amyloid A (SAA), N-terminal pro-brain natriuretic peptide (NTproBNP), and D-dimer. Compared with remission patients, non-remission patients presented with significantly higher LDH, neutrophil count, HS-TnT, CRP, SAA, procalcitonin (PCT), creatine kinase–MB mass (CKMB_M), NTproBNP, and D-dimer. In multivariate logistic regression analysis, we found that LDH [odds ratio (OR), 1.015; 95% confidence interval (CI), 1.006–1024; p = 0.001] and neutrophil count (OR, 1.352; 95% CI, 1.008–1.811; p = 0.044) were independently associated with exacerbation in COVID-19 patients. For ROC analysis, the AUC was 0.833 (95% CI, 0.729–0.936; p < 0.001) when we use the LDH value of 256.69 U/L to discriminate the ordinary pneumonia and severe pneumonia patients. The AUC was 0.759 (95% CI, 0.603–0.914; p = 0.008) and the sensitivity is 92.3% when we combined the LDH (cutoff value 258.46 U/L) and the neutrophil count (cutoff value 6.76 × 109/L) to discriminate remission and non-remission patients. Conclusion The level of LDH is associated with the severity of COVID-19 pneumonia and can be used as important indicators to evaluate the prognosis of patients.